What Multiple Myeloma With t(11;14) Should Be Classified Into in Novel Agent Era: Standard or Intermediate Risk? - Gao, Wen; Du, Juan; Liu, Junru; Zhou, Huixing; Zhang, Zhiyao; Jian, Yuan; Yang, Guangzhong; Wang, Guorong; Tian, Ying; Li, Yanchen; Wu, Yin; Fu, Weijun; et al. (Frontiers in Oncology, 2020)
Objective To investigate the prognostic value of t(11;14) for de novo multiple myeloma (MM) patients in novel agent era. Methods A total of 455 patients with fluorescence in situ hybridization (FISH), before treatments from three hospitals in China, were included in the study. All patients received autologous stem cell transplantation (ASCT) after induction therapy as consolidation. High risk (HR) cytogenetics were defined as t(4;14), t(14;16), and/or del 17p. Results A total of 152 patients were in the HR group. Of patients without HR cytogenetics, 55 were in the t(11;14) group, and 248 were in the standard risk (SR) group without t(11;14). Gain in 1q21 was observed in 38.9% patients with t(11;14). There were no differences in median progression free survival (PFS) and overall survival (OS), respectively, between patients in the t(11;14) group and those in the SR group. Patients in the t(11;14) group had the longer median PFS and OS, respectively, compared with those in the HR group. Regardless of coexisting with 1q21 gain or not, patients in the t(11;14) group still had similar median PFS and OS compared to those in the SR group. Finally, multivariate analysis indicated that including 1q21 gain and bone marrow plasma cell with CD20 expression, no variables were found to predict the outcome of the t(11;14) group in our cohort. Conclusions These results confirm that outcomes of t(11;14) MM are similar to standard risk patients when they receive novel agent induction therapy consolidated by ASCT. Gain of 1q21 coexists with t(11;14) frequently. In addition, both bone marrow plasma cell with CD20 expression and 1q21 gain have no impact on median PFS or OS for patients with t(11;14).